The Fighting Coast Guard : America's Maritime Guardians at War in the Twentieth Century, with foreword by Admiral Thad Allen, USCG (ret.) - Allen, Thad W.; Snell, Mark A. (Book collections on Project MUSE., 2023)
"This collection of essays, written by the some of the foremost historians in the field of Coast Guard history, highlights the wartime roles played by the United States' oldest federal maritime service, from its inception through the last decade of the twentieth century. It is organized into three distinct sections: "Beginnings"-which includes a short overview of the US Revenue Cutter Service (the USCG's primary forerunner, established in 1790) and two chapters on World War I; "Conflagration"-the role of the USCG during the World War II era; and "The Cold War and Beyond"-an assessment of the Coast Guard's participation in the Korean Conflict, the Vietnam War, and the Persian Gulf War of 1991. Because the Coast Guard operated as part of the Department of the Navy during the two world wars, its service and history is often overlooked or swallowed up by the larger service. The USCG's limited participation in cold and hot wars since 1945 is often ignored altogether. This anthology provides readers with a solid overview while highlighting some of the service's most important contributions as a combatant force"--